Correlations between Cytokine Levels, Liver Function Markers, and Neuropilin-1 Expression in Patients with COVID-19 - El Kazafy, Salma A.; Fouad, Yasser M.; Said, Azza F.; Assal, Hebatallah H.; Ali, Tarek M.; Ahmed, Amr E.; Elesawy, Basem H.; Ahmed, Osama M. (Vaccines (Basel), 2022)
Aim: The study evaluated the correlations between cytokine levels, liver function markers, and neuropilin-1 (NRP-1) expression in patients with COVID-19 in Egypt. The study also aimed to evaluate the accuracy sensitivity, specificity, and area under the curve (AUC) of the tested laboratory parameters in identifying COVID-19 infection and its severity. Patients and Methods: Fifty healthy subjects and 100 confirmed patients with COVID-19 were included in this study. COVID-19 patients were separated into two groups based on the severity of their symptoms. Serum ALT, AST, albumin, C-reactive protein (CRP), interleukin (IL)-1β, IL-4, IL-6, IL-18, IL-35, prostaglandin E2 (PGE2), and thromboxane A2 (TXA2) were estimated. We measured the gene expression for nuclear factor-kappa B p50 (NF-κB p50) and nuclear factor-kappa B p65 (NF-κB p65) and NRP-1 in blood samples using quantitative real-time polymerase chain reaction (qRT-PCR). AUC and sensitivity and specificity for cytokine levels and NF-κB p50 and NF-κB p65 and NRP-1 in identifying COVID-19 infection were also determined in both moderate and severe patient groups using receiver-operating characteristic curve (ROC) analysis. Results: All patients with COVID-19 showed higher serum activities of liver enzymes, levels of CRP, IL-1β, IL-4, IL-6, IL-18, IL-35 PGE2, and TXA2, and mRNA expression of NF-κB p50, NF-κB p65, and NRP-1 than healthy subjects. The severe group exhibited a significant increase in serum ALT, AST and IL-6 and a significant decrease in albumin, IL-1β, TXA2, and NF-κB p65 levels compared to the moderate group. In all patients (moderate and severe), all cytokines were positively correlated with NF-κB p50, NF-κB p65 and NRP-1 expression levels. Serum ALT and AST were positively correlated with CRP, cytokines (IL-4, IL-6, IL-18, IL-35 and TXA2), and NF-κB p50 and NF-κB p65 expression levels in both moderate and severe groups. They were also positively correlated with serum IL-1β level in the severe COVID-19 patient group and with NRP-1 expression in the moderate group. Using the logistic regression analysis, the most important four statistically significant predictors associated with COVID-19 infection in the study were found to be IL-6, TAX2, NF-κB p50 and NF-κB p65. ROC analysis of these variables revealed that three of them had AUC > 0.8. In moderate cases, AUC of the serum TXA2 level and NF-κB p65 expression were 0.843 (95% CI 0.517–0.742, p < 0.001) and 0.806 (95% CI 0.739–0.874, p < 0.001), respectively. In the severe group, AUC of serum IL-6 level was 0.844 (95% CI 0.783–0.904, p < 0.001). Moreover, Il-6 had a sensitivity of 100% in both moderate and severe groups. Conclusions: This study concluded that liver injury in patients with COVID-19 may be strongly attributed to the cytokines storm, especially IL-6, which was positively correlated to NF-κB p50, NF-κB p65 and NRP-1 mRNA expression levels. Moreover, ROC analysis revealed that IL-6, TXA2, and NF-κB p65 could be useful in predicting the possibility of infection with COVID-19, and IL-6 could be of possible significance as a good predictor of the severity and disease progress. However, RT-qPCR for SARS-CoV-2 detection is essential to confirm infection and further clinical studies are required to confirm this elucidation.